Bradymyces gen. nov. (Chaetothyriales, Trichomeriaceae), a new ascomycete genus accommodating poorly differentiated melanized fungi - Hubka, Vit; Réblová, Martina; Rehulka, Jiří; Selbmann, Laura; Isola, Daniela; de Hoog, Sybren G; Kolařík, Miroslav (Antonie van Leeuwenhoek, 2014)
Three slow growing, melanized and morphologically poorly differentiated fungal strains were isolated from a hyperaemic focus near the enlarged spleen of a farmed rainbow trout (Oncorhynchus mykiss) and from a rock collected at 3,200 m a. s. l. (Alps, Italy). Two phylogenetic analyses of the combined nuc18S and nuc28S rDNA and ITS rDNA and β-tubulin sequences showed that these isolates belong to the Trichomeriaceae, a family of the ascomycete order Chaetothyriales containing black yeasts that cause infections in humans and animals. The strains form a well-supported monophyletic clade. The new genus Bradymyces, with two new species, Bradymyces oncorhynchi and Bradymyces alpinus, is proposed based on phylogenetic, ecophysiological and morphological data. It is characterized by the presence of moniliform hyphae, blastic proliferation, endoconidia, multicellular and muriform bodies, and bodies with dark fragmented incrustations on the surface. Bradymyces most closely resembles members of Knufia. The ex-type isolate of B. oncorhynchi CCF 4369(T) ( = CBS 133066(T) = CCFEE 6134(T)) represents the first case of a Trichomeriaceae member isolated from cold-blooded water vertebrates. B. alpinus [ex-type strain CCFEE 5493(T) ( = CBS 138368(T) = CCF 4803(T))] is represented by two isolates from a single locality in the Alps and in contrast to B. oncorhynchi shows overall slower growth parameters and does not grow at 25 °C.
Keywords: Tubulin; Animals; RNA ribozomální 28S; Ascomycota; RNA, Ribosomal, 18S; ribozomální DNA; DNA, Ribosomal; RNA, Ribosomal, 28S; teplota; intergenová DNA; shluková analýza; Molecular Sequence Data; DNA, Fungal; Phylogeny; Temperature; tubulin; molekulární sekvence - údaje; RNA ribozomální 18S; Sequence Analysis, DNA; DNA fungální; Oncorhynchus mykiss; DNA, Intergenic; zvířata; sekvenční analýza DNA; Cluster Analysis; mikroskopie; fylogeneze; Microscopy; mikrobiologie životního prostředí; Environmental Microbiology